Aprendizagem colaborativa : uma proposta metodológica de construção do conhecimento em química orgânica - Marques, Ataiany dos Santos Veloso (2018)
This research presents the following scientific problem: How does the development of a proposed methodological of Collaborative Learning (AC) for the teaching of the concepts of carbonic chain contribute to Teaching-Learning Process in the subject chemistry for students of the 3rd grade of Integrated Secondary Education? It defends this thesis: "The proposed methodological AC contributes to Teaching-Learning Process the content of carbonic chain, promoting an active student’s posture of the, transform him protagonist this own learning process, also to favor the student individual and social development ". So, seeks to build, implement, and evaluate a proposal methodological teaching for the content of carbonic chains, in the subject chemistry of the Technician in Informatics course of the Federal Institute of Amazonas - IFAM, located in Parintins-Am/Brazil. This research is characterized as Qualitative, whose study’ object the teaching-learning process of carbonic chain for students for the Technician in Informatics Course starting by collaborative learning, this way it’s research the Case Study. The data collection was done through interviews with teachers, observation in the development of the proposed methodological, questionnaire applied to students and their regular documents (activities). From the results, it can be concluded that the Collaborative Learning contributes to the learning content of carbonic chain, provided better interaction between student-student and studentteacher; contributes to the development of social skills and future professional group interactions, promoted an active student posture, making him the protagonist of its own process. Was possible to verify that some students choose of the content transmission of carbonic chains. It was also to verify that for the teacher the proposed methodological contributed to the teaching-learning process, because proposes better interaction between students, helped in the learning of students who have difficulties in the learning and motivating their participation in the activities. We also perceive that some students are individualistic, competitive and totally focused on the best results in the test for the entrance examination.